GA3 treatments on seed germination in Rhodothamnus sessilifolius, an endangered species in Turkey - Nebahat Yıldırım; Müberra Pulatkan; Gülcay Ercan-O (Caldasia)
Rhodothamnus sessilifolius is a species of the Ericaceae familyendemic to the Artvin province in NE Turkey. This is in the critically endangered species list and current populations are decreasing, there-fore, it requires protection and reproduction. Thus the present study aimed to investigate the effect of various gibberellic acid (GA3) applications on germination of the R. sessilifolius seeds. The effects of various GA3 concentrations on final germination percentage, mean germination time, germination val-ue, and germination rate were analyzed in a growth cabinet. The study demonstrated that gibberellic acid application positively affected germination. Seed percentages of germination were 2.22 %, 18.89 %, 17.78 %, and 15.56 % in the control group for 100, 500 and 1000 ppm GA3 concentrations, respectively.First germination was observed in seeds treated with GA3 after 11 days. There were significant differ-ences (P < 0.05) between all measured germination properties. These results are promising for future conservation strategies.